Assessment of Awareness and Attitude on Cervical Cancer Prevention among Female Preparatory Students in Ziway town, Oromia Regional State, Ethiopia - Kifle, Kirubel; Kebede, Lidetu; Taye, Jiregna; Mekonnen, Abel; Ibrahim, Ismael; Abebe, Mekbib; Gezahegn, Meti; Ferid, Abdulhafiz; Mohammed, Arifullah; Hanif Reduan, Mohd Farhan (Asian Pacific Journal of Cancer Care, 2020)
Objective: Cervical cancer is common disease worldwide and ranks fourth among all malignancies for women. It has been reported to have been responsible for almost quarter of a million deaths annually, of which about 85% occurred in developing nations. Hence, the present study was conducted to assess the knowledge and attitude on cervical cancer prevention and its associated factors among female students in Batu Preparatory School, Ziway town, Oromia Regional State, Ethiopia in 2018. Methods: Institution based quantitative cross sectional study was conducted using anonymous self- administered questionnaire among female students in Batu Preparatory School in 2018. Results: Our results showed, the overall (62.1%) female preparatory students had heard of cervical cancer for most the source of information was mass media (50.7%). Though most has information on CC, only 33.3% were knowledgeable. Of the participants, 7.8% of had information about risk factor and 16% were aware of at least one of the symptom of CC. Results indicated that 72.5% of the participants believes that CC is preventable disease but only 21% had good knowledge on prevention. The overall positive attitude of the participants was 58.8%. Conclusion: Most participant believe that CC is preventable disease, and their knowledge on prevention is either poor or not satisfactory. In addition, most of the participants showed positive attitude towards CC prevention.